INSTRUMEN TES POTENSI AKADEMIK VISUALISASI SPASIAL/LOGIKA GAMBAR MODEL TIMBUL SEBAGAI INOVASI TEPAT GUNA UNTUK DIFABEL NETRA - Arditya Galih Fathurrohmah; Devi Ratnasari (Indonesian Journal of Fundamental Sciences, 2018)
is to validate the quality of the new instrument for a blind candidate college student. The result of our research is a potential academic test instrument for geometry logical test which is printed by an emboss technic. This instrument arises to effectively improve the ability to understand the meaning of the problem by students with disabilities. This is evidenced by the percentage of right answer to the 100% disabled when performing the matter in a way that is palpably independent, with minimal companion intervention.